MEMBANGUN SOCIAL NURTURANCE DI KALANGAN REMAJA DALAM RANGKA MENCEGAH KEKERASAN TERHADAP ANAK DI SMA KOLESE LOYOLA SEMARANG - Fransisca Iriani Roesmala Dewi; Ade Adhari; Luisa Srihandayani; Malvin Jati Kuncara Alam W (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Child violence cases are increasing in Indonesia. One cause of the increase is 'lack of community involvement with families'. The community often views violence against children as a natural way of educating children by parents, so there is no need for intervention from the community. This view needs to be changed with the socialization of the concept of social nurturance that every individual in society needs to participate to help children, not solely out of obligation, but as a necessity. Without realizing it,